1986
DOI: 10.1002/jso.2930330304
|View full text |Cite
|
Sign up to set email alerts
|

Giant leiomyoma of esophagus

Abstract: This case report of a 37-year-old man with giant leiomyoma details some of the problems encountered in diagnosing and treating this rare form of the disease. Initial studies at another institution were interpreted as demonstrating achalasia, and thoracotomy was later undertaken because of a mistaken diagnosis of a pericardiac mass, which led to a biopsy and a resulting esophagopleural fistula. Subsequent esophagectomy and drainage of empyema space were employed to remove the tumor, which had ulcerated and bled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…Over the years, minimally invasive surgery has caused a major paradigm shift from conventional open abdominal surgery. The excellent outcomes achieved in general surgery have been similarly demonstrated in thoracic surgery, with notable improvement in length of hospital stay, patient discomfort, and rapid return to preoperative activity . While thoracoscopic and laparoscopic enucleation of esophageal leiomyomas and other benign esophageal tumors is certainly a safe and effective operation, potential limitations to these techniques may be encountered.…”
Section: Discussionmentioning
confidence: 92%
“…Over the years, minimally invasive surgery has caused a major paradigm shift from conventional open abdominal surgery. The excellent outcomes achieved in general surgery have been similarly demonstrated in thoracic surgery, with notable improvement in length of hospital stay, patient discomfort, and rapid return to preoperative activity . While thoracoscopic and laparoscopic enucleation of esophageal leiomyomas and other benign esophageal tumors is certainly a safe and effective operation, potential limitations to these techniques may be encountered.…”
Section: Discussionmentioning
confidence: 92%
“…The resection site can be covered by pedicled pleural, omental, or muscular flaps [14][15][16][17]. Esophageal resection is advocated when the leiomyomas are large in size (>8 cm) or show a circular growth pattern [1,18], if the tumor is densely adhesive to the mucosa, or if extensive mucosal damage occurs accidentally during enucleation [11]. Leiomyoma are called "giant" when their size exceeds 10 cm [14].…”
Section: Discussionmentioning
confidence: 99%
“…There was no mortality in this series, although severe complications such as anastomotic leakage, chylothorax, and intrathoracic infection occurred. Colonic interposition was also performed in a giant esophageal leiomyoma measuring 20.5 cm and weighing 540 g [18], after an esophago-pleural fistula resulted from a biopsy. In the scope of increasing expectations upon minimal invasive surgery, Boone et al [21] recently reported on a successful robot-assisted thoracoscopic esophagectomy with the formation of a gastric conduit via laparotomy and a hand-sewn cervical anastomosis in a patient with a large 9×5×2.5-cmmeasuring leiomyoma.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported the incidence in the range of 0.005% to 7.9%. [1][2][3] The true incidence of esophageal leiomyoma, however, is debatable because many small lesions are asymptomatic and may not be diagnosed at the time of autopsy. The peak age of occurrence is between 30 and 59, and is rare in children.…”
Section: Introductionmentioning
confidence: 99%